Association of Smoking Status With the Risk of Type 2 Diabetes Among Young Adults: A Nationwide Cohort Study in South Korea. Issue 8 (15th February 2022) - Huh, Youn; Han, Kyungdo; Choi, Min-Jung; Kim, Jung Hwan; Kim, Seon Mee; Nam, Ga Eun
Abstract: Introduction: The longitudinal evidence between detailed parameters of smoking status and type 2 diabetes among young adults has been limited. We evaluated this association in young Korean adults. Methods: This nationwide cohort study included 3 026 551 adults aged 20 to 39 years who underwent Korean National Health Insurance Service health examinations in 2009 and were followed up until the end of 2017. The participants were categorized according to smoking status, smoking duration, and smoking amount. The hazard ratios (HRs) and 95% CIs for type 2 diabetes were estimated using multivariable Cox proportional hazard regression analysis. Results: During 8.2 years of follow-up, 71 952 cases of type 2 diabetes newly developed. Compared with never-smokers, independently increased HRs of type 2 diabetes were observed in ex-smokers (1.06, 95% CI = 1.04–1.09) and current smokers (1.39, 1.36–1.42). In these two groups, the type 2 diabetes risk increased with greater smoking duration and amount ( p for trend <.001). The HRs of type 2 diabetes were higher in current smokers than in ex-smokers at the same lifetime smoking amount. The associations between smoking status and incident type 2 diabetes were stronger in men, individuals who did not drink heavily, and those without obesity. Conclusions: Among young adults, past and current smoking was associated with an increased risk of type 2 diabetes, and there was a dose–response association of smoking amount and duration with type 2 diabetes development. Appropriate interventions to help young adults cease smoking may help reduce the incidence of type 2 diabetes. Implications: Smoking was associated with an increased risk of type 2 diabetes among young adults, and the risk was shown to increase as amount and duration of smoking increased. Ceasing smoking in young adults may help reduce the incidence of type 2 diabetes.